Μικρομετακινήσεις στους Νεολιθικούς Οικισμούς της Χοιροκοιτίας και επικινδυνότητα κατολισθήσεων - Χαριλάου, Στέλιος (Τμήμα Πολιτικών Μηχανικών και Μηχανικών Γεωπληροφορικής, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
In this diploma thesis we will monitor and analyze small transfers at specific locations in the Neolithic Settlement of Chirokitia Village based on measurements that we manage to make in two time periods: 19/05/2017 and 26/05/2017. The Leica GS15 and Trimple R9s instruments were used for the measurements, and the Leica Geo Office and Trimple Business Center software were used for the processed of the measurements. For the On-site we create a local reference system that was dependent on the permanent NICO reference station. The NICO reference station is part of the EUREF permanent network, which is a locally part of the IGS network that includes 160 permanent reference stations. After processing the measurements, it was observed that there were microtransfers in all directions with the highest recorded at altitude (0.014 m) while the horizontal displacements were in the scale of a few millimeters.
Keywords: Micro projections; GPS; GNSS; Μικρομετακινήσεις; Χοιροκοιτία; Τεκτονικές μετατοπίσεις